PEMBERIAN PUPUK ORGANIK CAIR RUMEN SAPI PADA PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Jene, Yohana; Indawan, Edyson; Prakoso D.J, Reza (Fakultas Pertanian, 2017)
This research aims to get the optimal dosage of organic fertilizer Liquid cow's Rumen that gives the plant the highest production growth, F1 Betavila Varieties. in the integrated Field Laboratory Faculty of Agriculture University of Tribhuwana Tunggadewi Tlaga, street colors, Sub Lowokwaru, Malang East Java During three months, calculated from May 28 to 9 August 2016.Research method of experimental design used in this study was a randomized Complete Design (RAL) consisting of 1 factor and 3-time repeats so there were 9 treatments. As for the treatment of liquid organic fertilizer dose Cow Rumen, i.e. as follows C1 32 ml. l-1 water, C2 40 ml. l-1 water, C3 48 ml. l-1 water, C4 56 ml. l-1 water, C5 64 ml. l-1 water, C6 72 ml. l-1 water, C7 80 ml. l-1 water, C8 88 ml. l-1 water, C9 96 l-1 ml. of water. Cow Rumen POC treatment with doses of 32 ml/l of water (C1) demons trating the existence of a real difference with other treatments. For the parameter number of leaves at age 28 HST with average 13.78 (strands), 42 HST with average 18.89 (strands) and the number of flowers at the age of 35 HST with average 10.33 (interest). Increased up to 40 HST, as time goes by. The absence of any real difference at high plant observation parameters (cm), the number of branches (branch), the amount of fruit (fruit), and the weight of the fruit (fruit) because all the doses of the POC has not been fullest for the growth and production of these parameters. Production of 271.87 g (C1) is equivalent to the outcome of. Penelitian ini bertujuan untuk mendapatkan dosis optimal Pupuk Organik Cair Rumen Sapi yang memberikan pertumbuhan produksi tanaman paling tinggi, Varietas Betavila F1. Pelaksanaaan di Laboratorium Lapangan Terpadu Fakultas Pertanian Universitas Tribhuwana Tunggaldewi, Jalan Tlaga warna, Kecamatan Lowokwaru, Malang Jawa Timur Selama tiga bulan, terhitung mulai 28 Mei sampai 9 Agustus, 2016. Metode penelitian Rancangan percobaan yang digunakan dalam penelitian ini ialah Rancangan Acak Lengkap (RAL) yang terdiri dari 1 faktor dan 3 kali ulangan sehingga terdapat 9 perlakuan. Adapun perlakuan dosis Pupuk Organik Cair Rumen Sapi, yaitu sebagai berikut C1 32 ml.l-1 air , C2 40 ml.l-1 air , C3 48 ml.l-1 air, C4 56 ml.l-1 air, C5 64 ml.l-1 air, C6 72 ml.l-1 air, C7 80 ml.l-1 air , C8 88 ml.l-1 air, C9 96 ml.l-1 air. Perlakuan POC Rumen Sapi dengan dosis 32 ml.l-1 air (C1) menujukan adanya perbedaan yang nyata dengan perlakuan lainnya. Untuk parameter jumlah daun pada umur 28 HST dengan 13,78 (helai), 42 HST dengan 18,89 (helai) dan jumlah bunga pada umur 35 HST dengan rata-rata 10,33 (bunga). Meningkat sampai dengan 40 HST, seiring berjalannya waktu. Tidak adanya perbedaan nyata pada parameter pengamatan tinggi tanaman (cm), jumlah cabang (cabang), jumlah buah (buah), dan berat buah (buah) karena semua dosis POC belum maksimal untuk pertumbuhan dan produksi parameter tersebut. Produksi sebesar 271,87 g (C1) setara dengan hasil konversi perhektar 45, 33 ton/ha sedikit lebih rendah dari hasil deskripsi varietas Betavila F1dengan produksi sebesar 46,59 ton/ha.